The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1051/0004-6361/201527661
|View full text |Cite
|
Sign up to set email alerts
|

Water and carbon dioxide distribution in the 67P/Churyumov-Gerasimenko coma from VIRTIS-M infrared observations

Abstract: Context. Studying the coma environment of comet 67P/Churyumov-Gerasimenko (67P) is one of the primary scientific goals of the VIRTIS experiment on the ESA Rosetta mission. Aims. The distribution and variability of water vapour and carbon dioxide in the comet's coma are needed to estimate their production rate, abundances in the nucleus, and the spatial distribution of the active regions. Methods. Infrared emission lines from vibrational bands of water and carbon dioxide at 2.67 and 4.27 µm, respectively, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 30 publications
10
75
0
Order By: Relevance
“…While it is difficult to exclude definitively any possibility, we consider it unlikely for super-volatiles to be the main driver of the observed changes. The observational evidence thus far indicates higher abundance of CO 2 from the unilluminated southern heminucleus (Hässig et al 2015) and, in particular, its depletion in Ma'at, Ash, Seth(-Hapi), and (Aten-)Babi regions in the northern hemi-nucleus where surface changes were detected (Bockelée-Morvan et al 2015;Fink et al 2016;Migliorini et al 2016). Podolak et al (2016) suggested that the measured CO 2 production rate, a few percent of water production, is insufficient to account for the typical speed of dust grains at meters per second.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While it is difficult to exclude definitively any possibility, we consider it unlikely for super-volatiles to be the main driver of the observed changes. The observational evidence thus far indicates higher abundance of CO 2 from the unilluminated southern heminucleus (Hässig et al 2015) and, in particular, its depletion in Ma'at, Ash, Seth(-Hapi), and (Aten-)Babi regions in the northern hemi-nucleus where surface changes were detected (Bockelée-Morvan et al 2015;Fink et al 2016;Migliorini et al 2016). Podolak et al (2016) suggested that the measured CO 2 production rate, a few percent of water production, is insufficient to account for the typical speed of dust grains at meters per second.…”
Section: Discussionmentioning
confidence: 98%
“…Heat propagation to x > 0.5 m would take longer than the time frame of surface changes, in which case, the observed changes would imply a (spatial) distribution of super-volatile ices in deeper subsurface. This scenario is contested by observations, if not excluded (Bockelée-Morvan et al 2015;Fink et al 2016;Migliorini et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…On the surface and in the depth of cometary nuclei, there are huge gradients of temperature, and the desorption of water or other molecules is spatially inhomogeneous and subject to diurnal variation (e.g. Bockelée-Morvan et al 2015;Lee et al 2015;Le Roy et al 2015;Migliorini et al 2016). Topological and geological diversity makes a comet a very rich but inhomogeneous medium.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis of the CO 2 outgassing has been done in Fink et al (2016) and will not be reported here. As shown in that paper and in the publications of Migliorini et al (2016) and Fougere et al (2016), CO 2 does not come from the illuminated northern hemisphere but rather from the dark but more primitive southern hemisphere. While the maximum of CO 2 in all this data set appears above the head region, we note that when we used the comet viewing program by Bieler to look down on the comet from the direction of the Sun, the CO 2 emissions along the LOS appear to originate from the terminator region separating the northern and southern hemispheres.…”
Section: The March 15 Data Setmentioning
confidence: 59%
“…In their work, the CO 2 -to-H 2 O column density ratio varies from 2 to 30 per cent, depending on the region observed. Migliorini et al (2016) reported that the H 2 O emission is mainly concentrated above two active regions, while the CO 2 distribution appears more uniform with significant emission coming both from the head and from the south latitude regions. In a comprehensive paper, Fink et al (2016) presented an investigation of the emission intensity of CO 2 and H 2 O and their distribution in the coma of 67P/CG.…”
mentioning
confidence: 99%